2018
DOI: 10.7554/elife.39625
|View full text |Cite
|
Sign up to set email alerts
|

LEAFY maintains apical stem cell activity during shoot development in the fern Ceratopteris richardii 

Abstract: During land plant evolution, determinate spore-bearing axes (retained in extant bryophytes such as mosses) were progressively transformed into indeterminate branching shoots with specialized reproductive axes that form flowers. The LEAFY transcription factor, which is required for the first zygotic cell division in mosses and primarily for floral meristem identity in flowering plants, may have facilitated developmental innovations during these transitions. Mapping the LEAFY evolutionary trajectory has been cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 94 publications
3
45
0
Order By: Relevance
“…In Arabidopsis , reproductive meristem identity is also controlled by the LEAFY transcription factor, and LEAFY activates MADS‐box gene expression in inflorescence and floral meristems to specify floral organ identity. Roles for LEAFY in regulating the reproductive transition are likely to be an innovation of seed plants as LEAFY homologue expression precedes MADS expression in Welwitschia cone development (Moyroud et al, 2017), but LEAFY homologues control apical proliferation in a fern (Plackett et al, 2018) and zygote proliferation in a moss (Tanahashi, 2005). A study of five Isoëtes species showed that LEAFY is expressed in proliferating vegetative and reproductive tissue, however this expression is diffuse and not localised to meristems (Yang, Du, Guo, & Liu, 2017).…”
Section: Analyses Of Gene Functions In Trait Evolutionmentioning
confidence: 99%
“…In Arabidopsis , reproductive meristem identity is also controlled by the LEAFY transcription factor, and LEAFY activates MADS‐box gene expression in inflorescence and floral meristems to specify floral organ identity. Roles for LEAFY in regulating the reproductive transition are likely to be an innovation of seed plants as LEAFY homologue expression precedes MADS expression in Welwitschia cone development (Moyroud et al, 2017), but LEAFY homologues control apical proliferation in a fern (Plackett et al, 2018) and zygote proliferation in a moss (Tanahashi, 2005). A study of five Isoëtes species showed that LEAFY is expressed in proliferating vegetative and reproductive tissue, however this expression is diffuse and not localised to meristems (Yang, Du, Guo, & Liu, 2017).…”
Section: Analyses Of Gene Functions In Trait Evolutionmentioning
confidence: 99%
“…Two LFY homologs from the lycophyte Isoetes L. ( IsLFY1 and IsLFY2 ) were observed to accumulate in both reproductive and vegetative tissues and are highly expressed in juvenile tissues 25 . Two LFY genes from the moss Physcomitrella patens were demonstrated to regulate the first mitotic cell division in zygotes 26 , while the LFY genes from the fern Ceratopteris richardii are required to maintain apical stem cell activity during shoot development 27 . These observations across distinct plant lineages, suggest that the non-reproductive functions of LFY may be ancestral 28 and make it possible to infer an evolutionary trajectory for this family.…”
Section: Introductionmentioning
confidence: 99%
“…Combined, LFY and its homologs represented an important gene family that promotes cell proliferation and which appears to have been progressively co-opted during evolution, adapted and specialized as more complex plant structures emerged 27 . For simplicity, in this broad-scale phylogenomic study, we refer to LFY and its homologs as LEAFY/LFY genes throughout, to avoid obfuscation generated by the presence of several other gene names reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In both ferns and angiosperms meristematic activity at the shoot apex is maintained by class I KNOX genes and LFY. These genes are also responsible for proliferative growth in the leaves of both ferns and angiosperms (e.g., compound leaves) (Tomescu 2009;Harrison & Morris 2017;Maugarny-Calès & Laufs 2018;Plackett et al 2018). Thus, determinacy of growth in leaves reflects the evolution of regulatory programs that repress these genes, such as the ARP group genes that repress KNOX I gene activity.…”
Section: Echoes Of Modularity 81 the Leaves Of Ferns And Seed Plantsmentioning
confidence: 99%